2015
DOI: 10.1016/j.bjid.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of human immunodeficiency virus and tuberculosis co-infected patients in public hospitals of eastern and southern zone of Tigray region, Ethiopia

Abstract: The rate of treatment success in this study was lower than the rate newly recommended by WHO. Therefore, efforts should be undertaken to improve treatment success rates of both diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
23
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 6 publications
(17 reference statements)
21
23
5
Order By: Relevance
“…This is in line with a similar report from the Tigray region, Ethiopia [36] and might be related with the lesser probability of females engaging in risky behaviours such as alcohol, substance, and tobacco abuse (observation). However, TB/HIV coinfection was significantly associated with the age groups of 25-34 and 35-44 years (aOR: 0.44; 95% CI: 0.25-0.8) and (aOR: 0.39; 95% CI: 0.2-0.7), respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with a similar report from the Tigray region, Ethiopia [36] and might be related with the lesser probability of females engaging in risky behaviours such as alcohol, substance, and tobacco abuse (observation). However, TB/HIV coinfection was significantly associated with the age groups of 25-34 and 35-44 years (aOR: 0.44; 95% CI: 0.25-0.8) and (aOR: 0.39; 95% CI: 0.2-0.7), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the proportion of patients with successful treatment outcomes (cured and completed) was found to be 90.9%, which is higher than the WHO target set for the Millennium Development Goal(MDG) of 85% [31][32][33] and comparable to that of the milestone target set globally for 2025 of > 90% [1,34].Comparable findings were reported by other Ethiopian studies [5,26,[35][36][37].…”
Section: Discussionsupporting
confidence: 53%
“…Patients with advanced immunosuppression, WHO stage III and IV during initial diagnosis of HIV, were linked with increased risk of unfavorable treatment outcome, consistent with the literature 14,19,28. Patients with advanced disease might be faced with multiple opportunistic infections and low CD4 count which directly affect TB treatment outcome.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, the study conducted in Northern Ethiopia showed that a CD4 count <200 cells/µL was associated with unfavorable outcome. Besides, WHO clinical stage IV and age >45 years were predictors of unfavorable outcome 19. The study conducted in Northwest Ethiopia reported that being bedridden and experiencing anti-TB medication side effects were associated with treatment failure 20…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate among HIV-positive tuberculous cases (20.0%) was significantly higher than those testing HIV negative (6.3%) and those not tested (8.9%). This finding is consistent with the reported death rate of 25.7% among HIV and tuberculosis co-infected patients in Ethiopia (16). It should be mentioned that HIV-positive cases in River Nile state receive antiretroviral therapy free of charge.…”
Section: Discussionsupporting
confidence: 91%